Baseline proteinuria level is associated with prognosis in idiopathic membranous nephropathy. (1st January 2019) - Chen, Xinxin; Chen, Yu; Ding, Xiaokai; Zhou, Ying; Lv, Yinqiu; Li, Duo; Chen, Bo; Chen, Tianxin; Chen, Chaosheng
Abstract: Objectives: This study aimed to investigate the unique prognostic, clinical, and renal histopathological characteristics of patients with idiopathic membranous nephropathy (IMN) with different levels of proteinuria. Methods: This retrospective observational study included 190 IMN patients with low levels of proteinuria (low group), 193 IMN patients with medium levels of proteinuria (medium group), and 123 IMN patients with high levels of proteinuria (high group) treated between September 2006 and November 2015. Prognostic and baseline clinical and histopathological data were compared among the three groups. Poor prognostic events included the occurrence of a persistent 50% reduction in estimated glomerular filtration rate (eGFR), end-stage renal disease, or all-cause mortality. Results: The severity of clinical symptoms and laboratory indices, such as blood pressure; extent of edema and hematuria; levels of fibrinogen, immunoglobulin (Ig)-G, complement (C)-4, total protein, albumin (ALB), and serum creatinine (SCr); and eGFR increased with increasing proteinuria (all p < .001). Based on renal histopathology, the extent of segmental sclerosis and balloon adhesion and renal interstitial lesion stage also increased in severity with increasing proteinuria (all p < .001). The Kaplan–Meier analysis showed that compared with patients with low and medium levels of proteinuria, patients with high levels of proteinuria had significantly lower cumulative poor event-free renal survival rates ( p = .0039). Conclusions: Baseline proteinuria level is indicative of prognosis in IMN patients; the greater the extent of proteinuria is, the worse the prognosis.